Self-Healing Hydrogels Formed by Complexation between Calcium Ions and Bisphosphonate-Functionalized Star-Shaped Polymers - Lopez-Perez, Paula M; da Silva, Ricardo M. P; Strehin, Iossif; Kouwer, Paul H. J; Leeuwenburgh, Sander C. G; Messersmith, Phillip B (Macromolecules, 2017)
Star-shaped poly(ethylene glycol) (PEG) chain termini were functionalized with alendronate to create transient networks with reversible cross-links upon addition of calcium ions. The gelation ability of alendronate-functionalized PEG was greatly dependent on the number of arms and arm molecular weight. After mixing polymer and calcium solutions, the formed hydrogels could be cut and then brought back together without any visible interface. After 2 min of contact, their connection was strong enough to allow for stretching without tearing through the previous fracture surface. Oscillatory rheology showed that the hydrogels recovered between 70 and 100% of the original storage and loss modulus after rupture. Frequency sweep measurements revealed a liquidlike behavior at lower frequencies and solidlike at high frequencies. Shifting frequency curves obtained at different calcium and polymer concentrations, all data collapsed in a single common master curve. This time–concentration superposition reveals a common relaxation mechanism intrinsically connected to the calcium–bisphosphonate complexation equilibrium.